Fungi in polar regions - Tsuji, Masaharu; Hoshino, Tamotsu (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
Fungi that inhabit polar-region can grow and decompose organic compounds under subzero temperatures play important roles in the nutrient cycle of polar-region ecosystems. Thus, changes in the mycoflora affect the ecological recycling in these regions, and understanding the cold-adaptation strategies of fungi under extreme environments is critical for a better understanding of polar-region ecosystems. Due to their ability to survive under extreme environments, fungi in polar-region are seen to show potential for utilization in biotechnologies. This book presents our current understanding of the mycoflora in polar-region and their cold adaptation strategies, and applied studies using their abilities.
"A science publishers book."
OCLC-licensed vendor bibliographic record.
Keywords: Fungi -- Polar regions; SCIENCE / Life Sciences / Biology; SCIENCE / Life Sciences / Microbiology; NATURE / Ecology; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / Biology / Microbiology